2017
DOI: 10.1016/j.ijintrel.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived overqualification on job satisfaction and career satisfaction among immigrants: Does host national identity matter?

Abstract: Overqualification is a form of person-job misfit that is common among those who reside in a foreign country. It is associated with poor work-related well-being and can inhibit full adjustment to the host society. The goal of our study is to examine the impact of perceived overqualification on job satisfaction and career satisfaction among immigrants. Furthermore, we investigated immigrants’ host national identity as a moderator of the impact of perceived overqualification on job satisfaction and career satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 93 publications
3
50
1
3
Order By: Relevance
“…To explore alternative explanations of the integration paradox, we combined the relative deprivation framework with the integration paradox literature. Whereas previous studies have stressed that a mismatch between educational level and economic position can affect one's mental well-being and life satisfaction (Wassermann, Fujishiro, and Hoppe 2017;George et al 2012), our study shows that such a mismatch does not influence migrants' destination country identification, even though this was one of the implicit suggestions in the paradox literature. In general, a higher educational level decreases migrants' sense of belonging in the Netherlands regardless of their economic position and a mismatch therewith.…”
Section: Conclusion and Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…To explore alternative explanations of the integration paradox, we combined the relative deprivation framework with the integration paradox literature. Whereas previous studies have stressed that a mismatch between educational level and economic position can affect one's mental well-being and life satisfaction (Wassermann, Fujishiro, and Hoppe 2017;George et al 2012), our study shows that such a mismatch does not influence migrants' destination country identification, even though this was one of the implicit suggestions in the paradox literature. In general, a higher educational level decreases migrants' sense of belonging in the Netherlands regardless of their economic position and a mismatch therewith.…”
Section: Conclusion and Discussioncontrasting
confidence: 93%
“…A mismatch between educational and economic position may resolve the integration paradox as it implies that it is not so much being successful in the structural domain which causes migrants to turn away from the destination country, but actually a mismatch between educational level and economic position that does so. That relative deprivation might matter indeed has been illustrated before, for instance by studies on life satisfaction (Grant 2008;Wassermann, Fujishiro, and Hoppe 2017). We argue that a mismatch between educational level and economic position can also bring about lower destination country identification.…”
Section: Mismatch Between Educational and Economic Positionsupporting
confidence: 60%
See 1 more Smart Citation
“…Past research has found proactive career behavious to be positively associated with subjective financial success, possibly protecting against the "pay" aspect of underemployment. Additionally, networking has been found to increase career and job satisfaction, known negative correlates of underemployment and perceived overqualification, and this relation has been evidenced among a recent graduate sample transitioning from college to work (Vos, Clippeleer & Dewilde, 2010;Kifle, Kler, & Shankar, 2018;Wassermann, Fujishiro, & Hoppe, 2017;Wolff & Moser, 2009).…”
Section: Proactive Career Behavioursmentioning
confidence: 99%
“…Perceived overqualification has also been conceptualized as a mismatch within a personjob fit framework, and has been examined alongside a number of organizational outcomes (Jansen & Kristof-Brown, 2006;Wassermann, Fujishiro, & Hoppe, 2017). Indeed, a recent meta-analysis examining 61 studies found that perceptions of overqualification were negatively related to job satisfaction, organizational commitment, and organizational behaviour, and positively related to turnover intentions and job search behaviours .…”
Section: Organizational Outcomes Of Subjective Underemployment and Ovmentioning
confidence: 99%